Cardiotoxicity of immune checkpoint inhibitors: A frequency network meta-analysis - Liu, Maobai; Cheng, Xitong; Ni, Ruping; Zheng, Bin; Huang, Shunmin; Yang, Jing (Frontiers in Immunology, 2022)
Immune checkpoint inhibitors (ICIs) in combination withother anti-cancer treatments have been approved for a variety of cancers. While the difference in the incidence of cardiovascular adverse events has not been fully investigated. We aimed to assess the the differences in cardiotoxicity among cancer patients receiving different ICI therapies. PubMed, Embase, Web of Science, Cochrane Library, and ClinicalTrials.gov. websites were searched for all randomized controlled trials (RCTs) of ICI. The primary outcomes were any grade cardiotoxicity and Grade 3-5 cardiotoxicity, the secondary outcomes were any grade myocarditis and Grade 3-5 myocarditis, with sub-analyses based on cancer type and does of ICI. A systematic review and frequency network meta-analysis were then performed for cardiotoxicity events. 91 RCTs (n=52247) involving 12 treatment arms were finally included. We observed that PD-L1 + CTLA-4 had the highest risk among all therapies inducing any grade cardiotoxicity, and the differences were significant except PD-1 + CTLA-4, PD-1 + TTD and PD-L1 + TTD. In addition, CTLA-4 had a higher risk of Grade 3-5 cardiotoxicity than PD-1 and anit-PD-L1. For Grade 1-5 myocarditis and Grade 3-5 myocarditis, no significant difference was found among differences therapies. No differences were observed in subgroup analyses according to does and cancer type. There were differences in the incidence of cardiotoxicity among different ICI therapies. For ICI monotherapy, CTLA-4 may be linked to Grade 3-5 cardiotoxicity than PD-1 or PD-L1. For dual therapy, the cardiotoxicity of dual ICI therapy seems to be higher than that of chemotherapy or targeted therapy.